Bunraku – intangible cultural heritage (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
Bunraku. Where puppets explain human emotions better than humans. Like Opera dei Pupi in Sicily, Italy, and Wayang in Indonesia, Ningyo Joruri Bunraku was designated a World Intangible Heritage by UNESCO in 2003 and enrolled on the list in 2008. It is one of Japan’s traditional performing arts, starting in the 17th century and continuing until today through Japanese history and culture. It combines narrative,  music, and puppets, each operated by three puppeteers. Because the puppets can showhuman emotions on the stage realistically, people all over the world are interested in it.Keywords: Japan. Bunraku. Puppet Theatre.